Age of first alcohol intoxication: Association with risky drinking and other substance use at the age of 20 (Swiss Medical Weekly, 2011)
QUESTION UNDER STUDY: To determine whether first alcohol intoxication before the age of 15 is associated with risky drinking patterns [Weekly Risky Drinking (WRD) and Binge Drinking (BD)], tobacco use, cannabis use at age 20 and other illicit substance use at somepoint within their lifetime. METHODS: A survey was conducted among 20-year-old French-speaking Swiss men attending the mandatory army recruitment process, using a self-administered questionnaire on alcohol and other substance use, as well as demographics (age, employment status, education level and living location). RESULTS: Of the 12’133 men attending the recruitment centre between January 2007 and September 2008, 9’686 were included in the study. Among them, 89% reported been intoxicated from alcohol at least once in the past, 11% reported WRD, 59% reported BD, 50% reported current tobacco use, 30% reported current cannabis use, and 19% reported other illicit substance use at somepoint within their lifetime. Subjects who reported first alcohol intoxication before age 15 were more likely to present current WRD (OR [95%CI]: 3.75[3.27–4.29]), BD (3.14[2.86–3.44]), current tobacco (3.17 [2.89–3.47]) or current cannabis use (3.26[2.97–3.58]), and other illicit drug use at somepoint within their lifetime (4.02[3.61–4.48]), than those who had a first intoxication at age 15 or older, or who had never been intoxicated. CONCLUSIONS: This study was consistent with the literature, and showed an association between age at first intoxication and future risky alcohol use patterns and other substance use at age 20. Although the results showing an association between age at first intoxication and later risky drinking do not necessarily imply causation, knowing the age of first intoxication may be useful to health care professionals in targeting adolescents and young adults who are at a high risk for developing alcohol and other substance use problems. As such, age at first intoxication may be used to identify vulnerable individuals in a clinical prevention setting.